New Perspectives in Critical Data Studies: The Ambivalences of Data Power - Hepp, Andreas; Jarke, Juliane; Kramp, Leif (Transforming Communications – Studies in Cross-Media Research, 2022)
This Open Access book examines the ambivalences of data power. Firstly, the ambivalences between global infrastructures and local invisibilities challenge the grand narrative of the ephemeral nature of a global data infrastructure. They make visible local working and living conditions, and the resources and arrangements required to operate and run them. Secondly, the book examines ambivalences between the state and data justice. It considers data justice in relation to state surveillance and data capitalism, and reflects on the ambivalences between an “entrepreneurial state” and a “welfare state”. Thirdly, the authors discuss ambivalences of everyday practices and collective action, in which civil society groups, communities, and movements try to position the interests of people against the “big players” in the tech industry. The book includes eighteen chapters that provide new and varied perspectives on the role of data and data infrastructures in our increasingly datafied societies.